Unstable Relationship Between Braarudosphaera bigelowii (= Chrysochromulina parkeae) and Its Nitrogen-Fixing Endosymbiont - Suzuki, Shigekatsu; Kawachi, Masanobu; Tsukakoshi, Chinatsu; Nakamura, Atsushi; Hagino, Kyoko; Inouye, Isao; Ishida, Ken-ichiro (Frontiers in Plant Science, 2021)
Marine phytoplankton are major primary producers, and their growth is primarily limited by nitrogen in the oligotrophic ocean environment. The haptophyte Braarudosphaera bigelowii possesses a cyanobacterial endosymbiont (UCYN-A), which plays a major role in nitrogen fixation in the ocean. However, host-symbiont interactions are poorly understood because B. bigelowii was unculturable. In this study, we sequenced the complete genome of the B. bigelowii endosymbiont and showed that it was highly reductive and closely related to UCYN-A2 (an ecotype of UCYN-A). We succeeded in establishing B. bigelowii strains and performed microscopic observations. The detailed observations showed that the cyanobacterial endosymbiont was surrounded by a single host derived membrane and divided synchronously with the host cell division. The transcriptome of B. bigelowii revealed that B. bigelowii lacked the expression of many essential genes associated with the uptake of most nitrogen compounds, except ammonia. During cultivation, some of the strains completely lost the endosymbiont. Moreover, we did not find any evidence of endosymbiotic gene transfer from the endosymbiont to the host. These findings illustrate an unstable morphological, metabolic, and genetic relationship between B. bigelowii and its endosymbiont.